2019
DOI: 10.2147/amep.s198789
|View full text |Cite
|
Sign up to set email alerts
|

<p>Publication rates of, and attitudes toward, summer research projects: 10-year experience from a single institution in New Zealand</p>

Abstract: Background: Research is increasingly being emphasized from an early stage in medical students’ careers. Medical student involvement in research and authorship of peer-reviewed manuscripts have been shown to enhance their academic performance—both in the short term and long term. The aim of this study was to evaluate outcomes and motivations of the summer studentship research program at our institution, using Vroom’s expectancy theory as a conceptual framework. Methods: We uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…4 Recently, studies have examined academic outcomes from these programmes and found them to result in tangible research outputs, with a journal publication rate ranging between 8.4-33%. [5][6][7][8] This is comparable to the average publication rate of medical student research worldwide (30%). 3…”
mentioning
confidence: 87%
“…4 Recently, studies have examined academic outcomes from these programmes and found them to result in tangible research outputs, with a journal publication rate ranging between 8.4-33%. [5][6][7][8] This is comparable to the average publication rate of medical student research worldwide (30%). 3…”
mentioning
confidence: 87%
“…Indeed, Alamri et al found that students with academic supervisors publish more often than those with non-academic clinicians as supervisor. 50 Previous research has not demonstrated that mandatory research in medical school leads to a more productive academic career. 9 22 This study provides a first insight in scientific engagement in the first years as medical doctor.…”
Section: Open Accessmentioning
confidence: 99%
“…Examples of various training pathways available globally are presented in Table 1. 9, [14][15][16][17][18][19] d u A dual medical-Doctor of Philosophy (PhD) programme is a structured pathway which offers students the opportunity to combine their medical training (i.e. a Doctor of Medicine [MD] degree) with a research-based degree (i.e.…”
Section: Global Clinical Academic Training Programmesmentioning
confidence: 99%
“…Studentships are a popular form of short-term supervised research experiences available to medical students in several countries. 9 , 19 , 35 Typically, students spend between 8–16 weeks of their summer vacation working on a research project. 9 , 19 , 35 Short-term research projects provide students with a chance to meaningfully contribute to the mainstream medical literature, with research showing that approximately one-third of studentships result in subsequent peer-reviewed publications.…”
Section: Global Clinical Academic Training Programmesmentioning
confidence: 99%
See 1 more Smart Citation